A survey of leaf phosphorus fractions and leaf economic traits among 12 co-occurring woody species on phosphorus-impoverished soils - Tsujii, Yuki; Fan, Baoli; Atwell, Brian J.; Lambers, Hans; Lei, Zhangying; Wright, Ian J. (Plant and soil, 2023)
Background and Aims The leaf economic spectrum (LES) is related to dry mass and nutrient investments towards photosynthetic processes and leaf structures, and to the duration of returns on those investments (leaf lifespan, LL). Phosphorus (P) is a key limiting nutrient for plant growth, yet it is unclear how the allocation of leaf P among different functions is coordinated with the LES. We addressed this question among 12 evergreen woody species co-occurring on P-impoverished soils in south-eastern Australia. Methods Leaf ‘economic’ traits, including LL, leaf mass per area (LMA), light-saturated net photosynthetic rate per mass (A mass ), dark respiration rate, P concentration ([P total ]), nitrogen concentration, and P resorption, were measured for three pioneer and nine non-pioneer species. Leaf P was separated into five functional fractions: orthophosphate P (P i ), metabolite P (P M ), nucleic acid P (P N ), lipid P (P L ), and residual P (P R ; phosphorylated proteins and unidentified compounds that contain P). Results LL was negatively correlated with A mass and positively correlated with LMA, representing the LES. Pioneers occurred towards the short-LL end of the spectrum and exhibited higher [P total ] than non-pioneer species, primarily associated with higher concentrations of P i , P N and P L . There were no significant correlations between leaf P fractions and LL or LMA, while A mass was positively correlated with the concentration of P R . Conclusions Allocation of leaf P to different fractions varied substantially among species. This variation was partially associated with the LES, which may provide a mechanism underlying co-occurrence of species with different ecological strategies under P limitation.